Decoding the evolutionary history of ST30 Staphylococcus aureus: insights into a potentially silent MSSA bloodstream pathogen - Esteves, Matheus Assis Côrtes; Carvalho, Mariana Fernandes; Viana, Alice Slotfeldt; Martini, Caroline Lopes; Longo, Luis Guilherme Araújo; Silva, Deborah Nascimento Santos; Ferreira, Adriana Lucia Pires; Ferreira-Carvalho, Bernadete Teixeira; Planet, Paul Joseph; Figueiredo, Agnes Marie Sá (Frontiers in Microbiology, 2025)
BackgroundStaphylococcus aureus clonal complex 30 (CC30) is a historically significant pathogen affecting both hospital and community settings. The notable pandemic clones, phage-type 80/81 (PT80/81) and the Southwest Pacific clone (SWP) have spread internationally, contributing to significant morbidity and mortality. Despite their importance, research on the evolution of sequence type (ST) 30 has been limited, often focusing on a small number of strains or specific regions.MethodsIn this study, we analyzed over 500 ST30 genomes from diverse sources, including Brazilian strains sequenced by our team, using genomic, pangenomic, phylogenetic, and time-calibrated phylogenetic analyses.ResultsWe traced key evolutionary events, estimating that the specialization of PT80/81 and SWP occurred after a divergence around 1868, forming a group of PT80/81-related strains and another group formed by SWP-related strains. Our findings highlight major events involving gene acquisition and loss, as well as mobile genetic elements (MGE). Notably, PT80/81 lost most lpl genes during diversification, which may have restricted the circulation of related strains. Contemporary strains—defined as those that emerged in the 21st century—predominantly cluster within a group divided into three subgroups, including Brazilian strains that acquired a novel pathogenicity island. Also clustering within the contemporary group, most toxic shock syndrome toxin-1 (TSST-1)-producing strains are methicillin-susceptible S. aureus (MSSA) that have gained additional virulence traits, including sea, which enhance their adaptability and virulence.ConclusionOur study revises the evolutionary history of ST30 S. aureus uncovering critical pathoadaptive events that may explain its success. Additionally, our findings emphasize a neglected issue: the high prevalence of MSSA in hospital infections, particularly the silent circulation of TSST-1 producing strains, capable of causing severe infections. Robust surveillance studies to monitor these strains are crucial.